The microbiome of the human skin and its variability in psoriasis and atopic dermatitis - Mazur, Małgorzata; Tomczak, Hanna; Lodyga, Martha; Czajkowski, Rafał; Żaba, Ryszard; Adamski, Zygmunt (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
The human organism is inhabited by very diverse microorganisms, which constitute the so-called human microbiome and are necessary for the proper functioning of the macroorganism. The correct microbiome ensures homeostasis of the body. A disturbance in its homeostasis leads to dysbiosis. Such deviations may also be related to the development of inflammatory skin diseases, including atopic dermatitis and psoriasis. This review aims to analyse the most current published data on the microbiome of the human skin and examine its role in cutaneous skin diseases, such as atopic dermatitis and psoriasis. This review was compiled by collaborating dermatologists specializing in atopic dermatitis and psoriasis. A comprehensive review of current literature was done using PubMed and limited to relevant case reports and original papers on the skin microbiome in atopic dermatitis and/or psoriasis. It has not been yet established whether changes in the microbiome are the cause or consequence of disease (atopic dermatitis/psoriasis). However, it was found that in the cases where pathological microflora predominated, an intensification of lesion severity is observed, while with clinical improvement, commensal microflora is restored. Modification of the composition of the microflora may lead to changes in the activation of the immune system and eventually to the development of inflammatory diseases. Adverse effects on the microbiome may include antibiotics, poor diet, stress and adverse environmental conditions. However, more research is needed to identify exact details and mechanisms.